2018
DOI: 10.20956/ijas.v6i2.1504
|View full text |Cite
|
Sign up to set email alerts
|

Quality and Storability of Mango During Zero Energy Cool Chamber (ZECC)

Abstract: Many researchhavefound thatthe use of zero energy coolchamber (ZECC) extend the shelf life of stored fruits and vegetables. There is a lack of study conducted in Indonesia about the use of ZECC to keep mangos after harvesting though. The present study, therefore, was aimed to understand the quality and storability of stored mangos in ZECC. Three different storage containers, a ZECC, ambient, and refrigerator with different average RH and temperature, were used to place selected ripe mangos (Mangifera indica L)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…cooler had less weight loss, only losing 2.8% weight, compared with a 5% weight loss for those stored in a conventional field shed. Similar results were reported by Dirpan et al (2018) where the loss in weight of mangoes was lower (3.1%) in cold storage when compared to 14.5% in storage at ambient conditions. The physiological loss of weight for French beans is a result of both the evaporation of water and respiratory losses (Olosunde et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…cooler had less weight loss, only losing 2.8% weight, compared with a 5% weight loss for those stored in a conventional field shed. Similar results were reported by Dirpan et al (2018) where the loss in weight of mangoes was lower (3.1%) in cold storage when compared to 14.5% in storage at ambient conditions. The physiological loss of weight for French beans is a result of both the evaporation of water and respiratory losses (Olosunde et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…The percentage weight loss increased with increase in storage period [19]. The increase in weight loss with storage period may be due to reduction in moisture content on respiration [10]. .…”
Section: Physiological Loss In Weightmentioning
confidence: 93%
“…Similarly, the ascorbic acid content of mango fruits stored in ABBEC were significantly higher than those in NBBEC and ambient storage conditions. This could be due to the relatively lower temperature and higher relative humidity which retards senescence through reduced respiration rate and other undesirable metabolic changes [10]. Bhushan [2] and Hossain et al [20] reported slightly lower values of 16 mg/100 g and within the range of 2.1 to 10.4 mg/100 g respectively.…”
Section: Physiological Loss In Weightmentioning
confidence: 99%
See 2 more Smart Citations